2008
DOI: 10.1007/s00066-008-1742-5
|View full text |Cite
|
Sign up to set email alerts
|

“Augmented Reality” in Conventional Simulation by Projection of 3-D Structures into 2-D Images

Abstract: The presented method provides an easy way to determine entity-specific safety margins related to patient setup errors upon registration of bony anatomy (prostate 0.9 cm for 90% of cases, breast 1.3 cm). The important role of planar X-ray imaging was clearly demonstrated. The innovation can also be applied to adaptive image-guided radiotherapy (IGRT) protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The mean shifts give the remaining systematic setup error for the case of conventional simulation alone. Since the average shifts are zero or close to zero in all directions, no systematic errors in our treatment planning and simulation process could be detected [3]. Table 1 shows how the systematic error and its SD vary with the number of CBCTs involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean shifts give the remaining systematic setup error for the case of conventional simulation alone. Since the average shifts are zero or close to zero in all directions, no systematic errors in our treatment planning and simulation process could be detected [3]. Table 1 shows how the systematic error and its SD vary with the number of CBCTs involved.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all patients received conventional simulation prior to radiation therapy resulting in the already low systematic errors. In a prior study with 158 patients, the average shifts observed at the simulation stage amounted 0.07 cm in L-R, 0.01 cm in C-C and -0.06 cm in A-P with SD of 0.36 cm, 0.24 cm and 0.43 cm, respectively [3]. In case of virtual simulation without "compensating" IGRT, larger treatment margins would have been necessary, namely 1.23 cm in the L-R, 1.21 cm in the C-C and 1.74 cm in the A-P direction.…”
Section: Tabellementioning
confidence: 99%
“…Augmented reality by projection of 3D structures into 2D images has also been attempted (16). However, a major drawback of such techniques is that the surgeon still does not have a real-time feedback from the imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate rotation compensation adapting gantry/collimator angle or MLC configuration [21] has been suggested. Robotic couches can perform rotational corrections, but the range of rotational motion is too small for prostate, where rotations up to 15° are observed, inducing substantial secondary patient displacements [33].…”
Section: Residual Uncertainties In Cbct-based Igrtmentioning
confidence: 99%